Access to levonorgestrel emergency contraception: science versus federal politics. (March 2013) - Thompson, Kirsten MJ; Raine, Tina R; Foster, Diana Greene; Speidel, J Joseph; Darney, Philip D; Brindis, Claire D; Harper, Cynthia C
Past US FDA decisions about emergency contraception (EC) have been subject to undue political influence, and last year's barring of over-the-counter access to Plan B One-Step ® for those under the age of 17 years is no exception. The US Department of Health and Human Services cited insufficient data on EC use for females aged 11–12 years. These youngest adolescents, however, rarely need EC: data from California (USA) show that in 2009, fewer than one in 10, 000 females under the age of 13 years received EC. Maintaining barriers to safe and effective EC is not medically necessary and conflicts with national goals to decrease teenage and unintended pregnancies.